(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(s): The purpose of our study was to evaluate clinical findings and sonographic features of abdominal wall endometriosis and also to report its CT and MRI appearance. Materials and methods: A retrospective study was performed from January 2008 - December 2012, yielding 12 surgically proven cases of abdominal wall endometriosis. All patients had undergone sonography including power Doppler examination. Additional CT was performed in one case and MRI in four. Pathological material was preoperatively obtained by sonographically guided puncture in six patients. The clinical data were analyzed and the imaging studies were reviewed by radiologist working in consensus. Results: All patients had a history of at least one prior cesarean section. All patients C/S was done in this institution and 1500 C/S were performed within a period of 5 years giving a frequency of 0.8% scar endometriosis after C/S. All presented with focal pain near the surgical scar, which was cyclic in three patients. Nine patients presented with a palpable mass near the scar. Sonography detected 11 lesions within the abdominal wall with a mean diameter 25mm and in one case sonography could not identify any lesion. All lesions were hypoechoic, vascular, and solid, with some cystic changes in one. MRI CT scan showed enhancement of the lesions. Finally histopathologically all were proved as endometriosis. Conclusion: Abdominal wall endometriosis frequently presents with noncyclic symptoms. Imaging findings of a solid mass near a cesarean section scar strongly suggest its diagnosis. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 3-8